2011
DOI: 10.1108/13552551111139656
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship barriers and entrepreneurial inclination among Malaysian postgraduate students

Abstract: Purpose -Postgraduate students who are more mature and have greater job experience are more likely to be inclined towards entrepreneurship. However, postgraduate students face various barriers such as lack of funds, fear of failure and lack of social networking that may hinder their entrepreneurial inclination. The barriers faced by these postgraduate students may also exhibit different dimensions compared with barriers faced by existing entrepreneurs. This study aims to examine the relationship between percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
107
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 74 publications
7
107
0
3
Order By: Relevance
“…In addition to personal traits, factors in the micro and macro environment that can encourage or hinder entrepreneurship have also been investigated (Franco et al, 2010;Franke & Luthje, 2003). Some of these environmental factors are: market structure and dynamics (Boccardelli & Magnusson, 2006;Van Stel, Storey, & Thurik, 2007); access to financing (Sara Carter, Shaw, Lam, & Wilson, 2007;Itani, Sidani, & Baalbaki, 2011a;Kim, Aldrich, & Keister, 2006;Sandhu, Sidique, & Riaz, 2011;Welsh, Memili, Kaciak, & Al Sadoon, 2014); government policy (Ahmad & Xavier, 2011;N. Carter, Brush, Greene, Gatewood, & Hart, 2003;Goby & Erogul, 2011;Minniti, 2008);political and economic stability (Lerner, 2010;Movahedi & Yaghoubi-Farani, 2012;Taylor & Plummer, 2003);culture and society's views on entrepreneurship (C. C. Baughn et al, 2006;C.…”
Section: Entrepreneurial Intention and Female Entrepreneurshipmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to personal traits, factors in the micro and macro environment that can encourage or hinder entrepreneurship have also been investigated (Franco et al, 2010;Franke & Luthje, 2003). Some of these environmental factors are: market structure and dynamics (Boccardelli & Magnusson, 2006;Van Stel, Storey, & Thurik, 2007); access to financing (Sara Carter, Shaw, Lam, & Wilson, 2007;Itani, Sidani, & Baalbaki, 2011a;Kim, Aldrich, & Keister, 2006;Sandhu, Sidique, & Riaz, 2011;Welsh, Memili, Kaciak, & Al Sadoon, 2014); government policy (Ahmad & Xavier, 2011;N. Carter, Brush, Greene, Gatewood, & Hart, 2003;Goby & Erogul, 2011;Minniti, 2008);political and economic stability (Lerner, 2010;Movahedi & Yaghoubi-Farani, 2012;Taylor & Plummer, 2003);culture and society's views on entrepreneurship (C. C. Baughn et al, 2006;C.…”
Section: Entrepreneurial Intention and Female Entrepreneurshipmentioning
confidence: 99%
“…Carter, Brush, Greene, Gatewood, & Hart, 2003;Goby & Erogul, 2011;Minniti, 2008);political and economic stability (Lerner, 2010;Movahedi & Yaghoubi-Farani, 2012;Taylor & Plummer, 2003);culture and society's views on entrepreneurship (C. C. Baughn et al, 2006;C. Baughn & Neupert, 2003;Gupta, Turban, Wasti, & Sikdar, 2009;Light & Dana, 2013;Ramadani, Gërguri, Dana, & Tašaminova, 2013;Shinnar, Giacomin, & Janssen, 2012);business information (Ettl & Welter, 2010;Sandhu et al, 2011);support mechanisms and networking opportunities (Ahmad & Xavier, 2011;Al-Alak & Al-Haddad, 2010;Caputo, Mehtap, et al, 2015;De Vita et al, 2014;Goby & Erogul, 2011);access to formal education and training (Dabic et al, 2012;Dickson, Solomon, & Weaver, 2008;Lüthje & Franke, 2002;Packham, Jones, Miller, Pickernell, & Thomas, 2010;Pruett, 2012).…”
Section: Entrepreneurial Intention and Female Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Personality traits like motivation (Iakovleva et al, 2014), courage and volition (Birdthistle, 2008), self-efficacy (Boyd & Vozikis, 1994;Zhao, 2005), confidence and fear, either in financial terms (Finnerty & Krzystofik, 1985) or in terms of risk avoidance (Giacomin et al, 2011;Singh Sandhu et al, 2011), are examined by many authors and are found to act either as drivers or as impediments to entrepreneurial intentions. For example, lack of motivation, lack of courage, lack of self-efficacy or confidence can act as personality constraints to one's engagement to self-employment.…”
Section: Internal Factorsmentioning
confidence: 99%
“…It is a measure of one's commitment to the target of establishing and running a new business (Kolvereid & Isaksen, 2006). Negative attitude towards entrepreneurship was declared as a barrier to entrepreneurship by many authors (Ledyaeva et al, 2008;Singh Sandhu et al, 2011;Smith & Beasley, 2011).…”
Section: Internal Factorsmentioning
confidence: 99%